Analisis Kualitas Pelayanan Dengan Kepuasan Nasabah Sebagai Variabel Intervening Terhadap Tingkat Loyalitas Nasabah Di PT. Pegadaian UPS Karang Bedil - Dina Ayulia Putri Lestari; Ida Bagus Eka; Putri Reno Kemala sari (Kredibel: Jurnal Ilmiah Manajemen, 2025)
This study aims to examine the quality of service with customer satisfaction as an intervening variable on the level of customer loyalty at PT. UPS Karang Bedil Pawnshop, Kediri District, West Lombok Regency. So that the research variables consist of one (1) independent variable, namely Service Quality (X), the intervening variable, namely Satisfaction (Z), and the dependent variable, namely Customer Loyalty (Y). The population of this study is people who have used and used services and products in PT. Pegadaian UPS Karang Bedil. The sample in this study uses no-probability sampling because the number of respondents is unknown. The samples taken were calculated using the Pau Leedy formula, the results obtained were 100 respondents. Data was obtained by distributing questionnaires to 100 customer respondents of PT. Pegadaian UPS Karang Bedil. Data was processed using SPSS 23. The results of this study indicate that service quality (X) and customer satisfaction (Z) have a positive and significant effect on customer loyalty, and customer satisfaction variable (Z) can mediate the effect of service quality (X) on customer loyalty (Y). ) at PT. Pegadaian UPS Karang Bedil. and The results of this study also show that the independent variable (Y) has a 61.6% influence on the Intervening Variable (Z), while the remaining 38.4% is explained by other variables. Then the results of this study also show that the independent variable (X) has a 77.8% influence on the Dependent Variable (Y), while the remaining 22.2% is explained by other variables that are not in the model.